GLP-1 receptor agonists downregulate aberrant GnT-III expression in Alzheimer's disease models through the Akt/GSK-3β/β-catenin signaling. (15th March 2018) - Wang, Ying; Chen, Song; Xu, Zheng; Chen, Suting; Yao, Wenbing; Gao, Xiangdong
Abstract: Alterations of glycoprotein glycans contribute to a wide variety of diseases. Bisecting N-acetylglucosamine (GlcNAc) levels increased in the cerebrospinal fluid of most Alzheimer's disease (AD) patients, and the mRNA levels of N-acetylglucosaminyltransferase III (GnT-III), a glycosyltransferase responsible for synthesizing a bisecting GlcNAc residue, were found highly expressed in the brains of AD patients. In our previous studies, glucagon-like peptide-1 (GLP-1) and its mimetics showed neuroprotective effects. Here, we confirmed that four weeks' treatment of exendin-4 could rescue memory deficits and neuropathological changes in APP/PS1 mice. We further explored the underlying mechanism and especially the role of GnT-III in it. We demonstrated for the first time that the levels of GnT-III and bisecting GlcNAc were increased in APP/PS1 mice and Aβ25-35 -treated PC12 cells, and GLP-1 receptor agonists (GLP-1RA) could downregulate aberrant neuronal expression of GnT-III and bisecting GlcNAc. We also found that GLP-1RA recovered the phosphorylation levels of Akt (Ser473) and GSK-3β (Ser9) and the levels of β-catenin in mice and cell models. Furthermore, the results indicated that inhibitor LY294002 attenuated these effects of GLP-1RA in PC12 cells, and β-catenin siRNA abolished the effect of GLP-1RA on GnT-III. In summary, our results suggest that GnT-III plays an important role in AD and GLP-1RA could downregulate aberrant GnT-III expression through the Akt/GSK-3β/β-catenin signaling pathway in neurons. Highlights: GnT-III and bisecting GlcNAc N-glycans were increased in APP/PS1 mice and Aβ25-35 -induced PC12 cell model. GLP-1RA prevented aberrant neuronal expression of GnT-III and bisecting GlcNAc N-glycans. GLP-1RA regulated GnT-III expression by activating the Akt/GSK-3β/β-catenin signaling in neurons.